Closure concepts for sustainable groundwater management: A case study - Meikle, C.D.; Skorulis, A.; Cupitt, P. (Mine Closure 2023: Proceedings of the 16th International Conference on Mine Closure, 2023)
To meet the growing technical demand of regulators and independent panels, enhanced engineering and scientific assessment are required to demonstrate the feasibility and environmental sustainability of mine closure concepts. This case study supports the development of viable mine closure concepts for groundwater management for an operational underground resource project in New South Wales, Australia. In this study, the establishment of differential groundwater repressurisation is designed to address the concerns of regulator and independent technical panels, that post-closure mine water outflow may discharge at uncontrolled locations, triggering land instability along an extensive ~300 m high escarpment. An innovative rationale was adopted to enable sustainable post-closure inflow and outflow management, with enhanced environmental outcomes, namely achieving groundwater repressurisation in sought-after locations limiting impacts on slope stability and providing long-term passive outflow management. The concept design considered the existing and future mine layout, groundwater behaviour, geomechanics and downstream water management infrastructure as an integrated system. A three-dimensional numerical groundwater model was used to validate technical feasibility, supported by engineering first principles, industry standards and relevant case studies from other operations. The configuration of groundwater recharge and outflow management were assessed under the following categories 1) the viability, location and impacts of bulkheads (mine seals) and their effects to the groundwater system; 2) post-closure groundwater system recovery and quantification of mine water outflow; and 3) long-term water quality and management. Contrary to typical rationales, the objective of the design was not to completely seal or prohibit outflow of water from the mine, but to control groundwater recovery and subsequent outflow through the natural permeability of the surrounding strata, directing it to a controlled location. Similarly, rather than adopting bulkheads (seals) near or at mine portals, modulation bulkheads were devised deep within the workings to achieve target groundwater recovery in desired locations, but also limit recovery in areas of historical adjacent mining. The methodical placement of bulkheads in the groundwater model determined a means to reduce the risk of groundwater repressurisation interacting with anthropogenic and environmental flow pathways. The integrated system was modelled to predict future outflow rates and volumes, calibrated by contemporary in-situ testing and monitoring. Predicted outflow metrics were incorporated with long-term water quality observations to develop a series of viable post-closure passive and active treatment options, to be further evaluated closer to closure. This case study demonstrates the benefits of effective collaboration between hydrogeologists, geotechnical engineers, hydrologists and water quality specialists in the identification of post-closure risks and the development of sustainable groundwater management solutions.